Tubo-ovarian Abscess and Uterine Leiomyoma in a 35-year-old woman with 8 years of infertility: A Case Report - Cipta Pramana1 , Kartika Budi Peranawengrum1 , Jennifer Nanda Dewi1 , Charity Harlim1 , Victor Sepri (Indian Journal of Forensic Medicine & Toxicology, 2021)
Infertility can be influenced by several factors, including the presence of leiomyomas and tubal abnormalitieslike a tubal abscess or tubo-ovarian abscess which can cause adhesions of the tubes and surrounding tissuesor obstruction of the tubes. A 35-year-old woman is diagnosed with primary infertility of 8 years withintramural uterine leiomyoma, right tubo-ovarian abscess, and left tubal abscess with tubal obstruction.Laparotomy myomectomy and salpingostomy surgery were carried out. There were no complications duringor after the surgery. The management of infertile patients with leiomyoma and tubo-ovarian abscess whowish to preserve reproductive function requires special attention.